Non-equilibrium phase transition of two-dimensional penta-graphene - Nguyễn, Nguyễn Thị Bảo Trang; Lê, Hoàng Nhân; Trương , Quốc Tuấn; Nguyễn , Trúc Anh; Đặng, Minh Triết (Hue University Journal of Science: Natural Science, 2021)
Graphene has received enormous attention in the semiconductor industry during the last two decades. However, since graphene is a gapless semiconductor, it has critical challenges to be engineered into semiconductor devices. Recent reports have shown that penta-graphene stands out as a promising semiconductor candidate with an electronic bandgap between 2.2 and 4.3 eV; thus, it can surmount graphene’s obstacles. However, when being heated, penta-graphene can transform its configurations from pentagonal lattices to hexagonal graphene-like heterostructures, resulting in a significant electronic modification. In this paper, we investigate the effect of heating rates on the non-equilibrium phase transition of a two-dimensional penta-graphene by using molecular dynamic simulations. We have shown that, with a fast-heating process, penta-graphene naturally transforms to graphene without a clear phase separation point. Nevertheless, with a sufficiently slow heating protocol, this transition is a first-order phase transition from a pentagonal to a more stable hexagonal configuration. These results provide the possibility to implement penta-graphene in future optoelectronic devices.